2002
DOI: 10.1007/bf03343978
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of circulating levels and renal clearance of natural amino acids in patients with Cushing’s disease

Abstract: Although the hypercortisolism-induced impairment of protein homeostasis is object of several studies, a detailed evaluation of the complete amino acid profile of patients with Cushing's syndrome (CS) has never been performed. The aim of the current open transversal controlled study was to evaluate serum and urinary concentrations as well as renal clearance of the complete series of natural amino acids and their relationship with glucose tolerance in patients with Cushing's disease (CD). Twenty patients with CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…Phe was evaluated with a standardized quantitative enzymatic assay, in dried blood samples on filter paper (2992 Schleicher-Schull) with R&D Diagnostics Ltd reagens (Wendel et al, 1990). Tyr levels were evaluated in plasma as described by Faggiano et al (2002), CV 1.8%. Lipid variables were measured spectrophotometrically with a routine method, using commercially available kits.…”
Section: Methodsmentioning
confidence: 99%
“…Phe was evaluated with a standardized quantitative enzymatic assay, in dried blood samples on filter paper (2992 Schleicher-Schull) with R&D Diagnostics Ltd reagens (Wendel et al, 1990). Tyr levels were evaluated in plasma as described by Faggiano et al (2002), CV 1.8%. Lipid variables were measured spectrophotometrically with a routine method, using commercially available kits.…”
Section: Methodsmentioning
confidence: 99%
“…The involvement of renal structure and function in the clinical picture of CS is represented by the occurrence of nephrolithiasis and the impairment of renal clearance (15,16). Silent microlithiasis were the most common clinical expression of nephrolithiasis in patients with active disease, associated with hypercalciuria, hyperuricosuria, increased urinary levels of oxalate and decreased urinary levels of citrate.…”
Section: Renal Diseasesmentioning
confidence: 99%
“…Glucocorticoid excess exerts multiple and complex effects on the skeletal system, including osteopenia or osteoporosis, often associated with pathological fractures (11,12), osteoarthrosis (13), and osteonecrosis (14). Nephrolithiasis, together with an impairment of renal function, is also quite common, although it is usually not associated to a clinical syndrome (15,16). Mental disturbances complicate great part of patients with CS and include a range of psychological or psychiatric manifestations ranging from anxiety to psychosis, such as major depression, and intellective impairment involving cognition and memory, often associated with cerebral atrophy (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…In both studies they reported that patients with Cushing's disease (active and cured) showed a lower clearance than controls, but the difference was not statistically significant. When we compare our study results with those of Faggiano et al (9,10) we notice that their control group did not include overweight individuals. When GFR was estimated by the Cockroft -Gault equation we found no statistical differences between our cases and controls.…”
Section: Discussionmentioning
confidence: 70%
“…In two previous studies Faggiano et al (9,10) determined the creatinine clearance using a 24-h urine collection. In both studies they reported that patients with Cushing's disease (active and cured) showed a lower clearance than controls, but the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%